Alzheimer's diagnosis system based on magnetic resonance imaging using the VGG16 algorithm (Latin-American Journal of Computing, 2024)
Early diagnosis of Alzheimer's disease is essential to provide timely treatment to patients. In this regard, a system for diagnosing Alzheimer's disease based on magnetic resonance imaging and utilizing a convolutional neural network algorithm called VGG16, has been developed. Magnetic resonance images of patients with and without Alzheimer's disease were collected and processed. These images were used to train the algorithm, which learned to identify and associate patterns with the disease. Subsequently, tests were performed with a set of unseen images to evaluate the diagnostic ability of the system. Through the analysis of magnetic resonance images, the VGG16 algorithm has shown a capacity of over 82% to correctly recognize these signs. These results validate the effectiveness of the artificial intelligence-based approach for diagnosing Alzheimer's disease.